Dilated Cardiomyopathy Compatible With Sarcoidosis Presenting with Syncope Due to Torsades de Pointes: a Case Report - Tinoco, Carollina Fernandes; Branca, Nathalia Rodrigues Perrenoud; Carvalho, Gabriela Domingues; Faria, Lívia Silva de Paula; Nascimento, Erivelton Alessandro do (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Sarcoidosis is a multisystemic noncaseating granulomatous disease of unknown etiology. Cardiac sarcoidosis clinical presentation is diverse, and syncope is one of the possible primary events. Due to its variable natural history and initial presentation associated with lacking sensitive and specific diagnostic tests, it still represents a challenging diagnosis. This article presents the case of a 51-year-old female patient with intermittent syncope events associated with torsades de pointes and dilated cardiomyopathy compatible with sarcoidosis.